Reassembling Formal Features in Articles by L1 Persian Learners of L2 English - Marjansadat Momenzadeh; Manijeh Youhanaee (Applied Research on English Language, 2015)
There has been considerable debate over what the sources of morphological variation in second language acquisition are. From among various hypotheses put forth on the topic, the feature reassembly hypothesis (Lardiere, 2005) assumes that it is the reconfiguration of features in the L2 which causes variation between the performance of natives and non-natives. Acknowledged as one of the most difficult elements of English grammar to be acquired by learners, the article system was the focus of the present study which aimed at attending to the acquisition of that system by Persian learners. This descriptive piece of research focused on how the article system functions in English and Persian, the similarities found across the two languages and the possible sources of difficulty for Persian learners in using English articles as related to their L1. The participants included Persian learners at three levels of grammatical knowledge. A group of English native speakers also took part in the study. A grammaticality judgment test and a translation test were conducted to collect data. Comparisons were made among the four groups, using ANOVAs. Based on the results, it is argued that the observed pattern of article use among Persian speaking learners can be best accounted for by the feature reassembly hypothesis.